Dimensi-Dimensi Iman dalam Ibrani 11:1–31 : Kajian Eksegetikal Teks Yunani Koine untuk Penguatan Teologi Iman Kristen. - Sipayung, Gerhard; Gultom, Patar Aprizal (Sekolah Tinggi Teologi Sola Gratia Medan, 2025)
Abstract. This Journal examines the dimensions of faith in Hebrews 11:1–31 through an exegetical analysis of the original Koine Greek text. The study aims to explore the theological meaning of the word pistis (faith) within the various narrative contexts of Old Testament figures mentioned in the passage, as well as its implications for the life of Christian believers today. The methodology includes morphological, syntactical, and semantic analysis of the Greek text, along with a literature review of scholarly journals and reputable biblical commentaries. The findings indicate that faith in Hebrews 11 is portrayed as an active ontological-epistemological reality, encompassing an integral ethical-relational dimension, and oriented toward an enduring eschatological hope that sustains the life of the faithful. Abstrak. Jurnal ini mengkaji dimensi iman dalam Surat Ibrani 11:1–31 berdasarkan analisis teks asli Yunani Koine secara mendalam secara eksegetikal. Penelitian ini bertujuan menggali makna kata πίστις (iman) dalam berbagai konteks naratif tokoh Perjanjian Lama yang disebutkan, serta implikasi teologisnya bagi kehidupan beriman umat Kristen masa kini. Metode yang digunakan adalah analisis morfologi, sintaksis, dan semantik teks Yunani, serta kajian pustaka dari jurnal ilmiah dan komentar Alkitab terkemuka. Hasil kajian menunjukkan iman sebagai realitas ontologis-epistemologis yang aktif, dimensi etis -relasional yang integral, serta pengharapan eskatologis yang berkelanjutan.